2010
DOI: 10.1212/wnl.0b013e3181c7197b
|View full text |Cite
|
Sign up to set email alerts
|

25-Hydroxyvitamin D levels and cognitive performance and decline in elderly men

Abstract: Objective: To The prevalence of 25 hydroxyvitamin D [25(OH)D] deficiency, defined as 25(OH)D level less than 20 ng/mL, is high, especially among the elderly, with 25% to 65% affected. [1][2][3][4][5][6] While much research has focused on the adverse effect of 25(OH)D deficiency on bone health, 5,7 associations between 25(OH)D deficiency and non-bone health outcomes, including hypertension, 8 cardiovascular morbidity, 9 diabetes, 10,11 and cancer, 12,13 have also been reported. In addition, there is a growin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
139
4
8

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(159 citation statements)
references
References 37 publications
8
139
4
8
Order By: Relevance
“…Most of the other studies that investigated the association between cognitive performance and vitamin D status did not stratify the analysis by sex. However, Slinin et al (2010) recently reported that they found little evidence of independent associations between lower 25(OH)D level and baseline global and executive function, or indeed, cognitive decline in a cohort of 1603 men aged X65 years. A recent cross-sectional study carried out in an all-female cohort (n ¼ 752; aged 75 þ years) reported that communitydwelling women with low serum 25(OH)D concentrations (p25 nmol/l) had significantly poorer scores in the Pfeiffer Short Portable Mental State Questionnaire (a screening tool for dementia) compared with women with concentrations of 425 nmol/l (Annweiler et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the other studies that investigated the association between cognitive performance and vitamin D status did not stratify the analysis by sex. However, Slinin et al (2010) recently reported that they found little evidence of independent associations between lower 25(OH)D level and baseline global and executive function, or indeed, cognitive decline in a cohort of 1603 men aged X65 years. A recent cross-sectional study carried out in an all-female cohort (n ¼ 752; aged 75 þ years) reported that communitydwelling women with low serum 25(OH)D concentrations (p25 nmol/l) had significantly poorer scores in the Pfeiffer Short Portable Mental State Questionnaire (a screening tool for dementia) compared with women with concentrations of 425 nmol/l (Annweiler et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Buell et al (2009) found a positive association between serum 25(OH)D and primary measures of executive functioning and attention processing speed in elderly adults. However, other data on the association between vitamin D status and cognitive function in humans are inconsistent (Jorde et al, 2006;Wilkins et al, 2006;McGrath et al, 2007;Slinin et al, 2010), possibly owing to the use of different cognitive batteries, some of which may have been inappropriate for the type of study/patient group (see review by Buell and Dawson-Hughes, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] The January 2010 issue of Neurology contained 3 studies that evaluated hundreds of elderly subjects to test for a relationship between vitamin D status and dementia or cognitive impairment. 4,8,9 The Annweiler and Buell studies evaluated women only and both women and men, respectively; both showed a significant relationship between low vitamin D and dementia or cognitive impairment. The Slinin report only evaluated men and showed a trend for a relationship between vitamin D and cognitive impairment.…”
mentioning
confidence: 99%
“…The IOM concluded that children aged 0-1 year require 400 IU/daily vitamin D (corresponding to 10 mg/daily vitamin D, being 1 mg vitamin DZ40 IU), all other children and adults up to the age of 70 years require 600 IU/day (15 mg/day) and adults over the age of 70 years need 800 IU/day (20 mg/day). On the contrary, the ES recommended a dose of vitamin D ranging from 400 to 1000 IU/day (10-25 mg/day) for children aged 0-1 year, 600-1000 IU/day (15-25 mg/day) for children aged more than 1 year, and 1500-2000 IU/day (37.5-50 mg/day) for adults aged 18 years or more (9,10). Moreover, the ES also recognized that obese children and adults may require as much as two to three times the recommended dose due to the influence of body fat on vitamin D storage and metabolism (67).…”
Section: Vitamin D and Supplementation: General Considerationsmentioning
confidence: 99%
“…This interest, also shared by the lay community, mainly derives from the recognized effect of vitamin D on mineral metabolism and neuromuscular function (1,2) and the purported effect on other aspects of health: cardiovascular (3,4,5), endocrine (6,7), metabolic (8), neurological (9,10), neoplastic (11), articular (12), immunological (13,14), etc. Furthermore, vitamin D has also been linked to mortality (15,16).…”
Section: Introductionmentioning
confidence: 99%